Peningkatan Kapasitas Petani melaui Pelatihan dan Pendampingan Pembuatan Pupuk Organik Di Desa Fafoe Kecamatan Malaka Barat, Kabupaten Malaka - Naikofi, Kristina Irnasari; Pareira, Magdalena Sunarty; Banunaek, Zofar Agluis; Naisanit, Gregoriana; Fanu, Arnoldina; Sesnae, Claudius (Kadiri University, 2025)
Fafoe Village in West Malaka District, Malaka Regency, has great potential for cultivating horticultural vegetables, particularly white mustard greens (Brassica pekinensis L.). However, farmers in this village face a major obstacle: a lack of knowledge about organic fertilizer production and efficient, environmentally friendly cultivation techniques. The Professional Work Lecture (KKP) program aims to increase farmer capacity by providing training and mentoring in the production of organic fertilizer based on livestock waste and improving cultivation techniques. The method employed was participatory training and continuous mentoring, which lasted for four weeks. The effectiveness of this approach was measured through pre- and post-tests, designed to assess improvements in farmers' knowledge and skills. The evaluation results showed an average increase in understanding of 52.6%. Additionally, 50% of farmer group members were able to independently produce and apply organic fertilizer to their cultivated land, which has had a positive impact on crop productivity and farmer economic well-being. This program shows potential as a model for sustainable agricultural development in other rural areas with similar contexts. Desa Fafoe di Kecamatan Malaka Barat, Kabupaten Malaka memiliki potensi besar dalam budidaya sayuran hortikultura, khususnya sawi batang putih (Brassica pekinensis L.). Namun, petani di desa ini menghadapi kendala utama berupa kurangnya pengetahuan tentang pembuatan pupuk organik serta teknik budidaya yang efisien dan ramah lingkungan. Program Kuliah Kerja Profesi (KKP) bertujuan untuk meningkatkan kapasitas petani dengan memberikan pelatihan dan pendampingan dalam pembuatan pupuk organik berbasis limbah ternak serta teknik budidaya yang lebih baik. Metode yang digunakan adalah pelatihan partisipatif dan pendampingan berkelanjutan selama empat minggu, dengan pengukuran efektivitas melalui pre-test dan post-test untuk mengetahui peningkatan pengetahuan dan keterampilan petani. Hasil evaluasi menunjukkan peningkatan pemahaman rata-rata sebesar 52,6% dan sebanyak 50% petani anggota kelompok tani mampu memproduksi pupuk organik secara mandiri serta mengaplikasikannya di lahan budidaya, yang berdampak positif pada produktivitas tanaman dan kesejahteraan ekonomi petani. Program ini menunjukkan potensi sebagai model pengembangan pertanian berkelanjutan di wilayah pedesaan lain dengan konteks serupa.